(untitled) (Филолошки студии, 2019)
Mora is a nocturnal female demonic creature who draws her strength and life juices out of a sleeping person. Although there are different apotropes against Mora, she can be lethal, especially if her potential victims are children. When investigating this female demonic being we have to start from ancient Slavic religious system through which reconstruction do we come to Croatian pagan mythic images. Mora as a nocturnal female demon can be related to Morana, who in the ancient Slavic religious system was the godess of winter and death. Tales of Mora are still present in the storytelling of Croats in Bosnia and Herzegovina. Interpretation of modern tales of Mora recorded among BiH Croats will show how Mora from these stories significantly resembles Morana, originally a young and joyful girl and bride at a divine wedding, and later an abandoned wife and a fearsome vigilante from the Croatian pagan mythology.